Comparative effectiveness of various educational approaches on oral hygiene in pediatric populations - Dilşah Çoğulu; Eylül Ebrar Ömeroğlu; Buse Nur Çınar (BMC Digital Health)
Abstract Background Dental caries constitutes a major global public health challenge, posing substantial burdens on both oral health outcomes and healthcare systems worldwide, with far-reaching implications for prevention, treatment, and economic resources. Regular tooth brushing recognized as the most effective preventive way against dental caries. However, motivating children to adopt and maintain proper oral hygiene behaviors remains a significant challenge. This study aims to evaluate and compare the effectiveness of traditional education methods and a mobile application in promoting oral hygiene habits among children. Methods The study included 150 children who attended routine dental examinations. Parents were completed a baseline questionnaire to assess their child’s oral hygiene habits. Baseline clinical measurements were recorded, including dental caries indices (dft/DMFT, dfs/DMFS), dental plaque, and gingival index scores. Participants were randomly allocated into three groups: Group-1: received individualized oral hygiene instruction using a model and toothbrush; Group-2: received slide-based oral hygiene education; and Group-3: utilized mobile application. After six months, follow-up assessments were conducted, including a repeated parental questionnaire, clinical evaluations, and a parental satisfaction survey. Statistical analyses were performed using SPSS 25.0 with chi-square, Kruskal–Wallis, and Fisher’s Exact tests. Results All three groups demonstrated significant reductions in dental plaque and gingival index scores, with improvements in oral hygiene behaviors observed across interventions (p < 0.05). While participants in the mobile application group exhibited the most favorable numerical outcomes, the differences among the three intervention groups were not statistically significant. 93% of parents expressed their satisfaction with the educational methods. Conclusions The findings indicate that digital interventions, including mobile applications, may serve as useful tools for supporting oral hygiene motivation in children, although further evidence is needed to establish their comparative effectiveness. Trial registration [Full registry name: Comparative Effectiveness of Various Educational Approaches on Oral Hygiene], registered on [Date: March 27, 2025]. [Retrospectively registered](NCT06910501).